Protracted localization of metamorphism and deformation in a heterogeneous lower-crustal shear zone - Zertani, Sascha; Menegon, Luca; Pennacchioni, Giorgio; Buisman, Iris; Corfu, Fernando; Jamtveit, Bjørn (Journal of Structural Geology, 2023)
Deformation of the continental crust is influenced by the pre-existing structural framework, fluid availability, strain rate, and pressure-temperature conditions. We investigate the evolution of a large (hundreds-of-meters wide) heterogeneous shear zone and associated brittle and ductile deformation structures (Lofoten, Norway) using structural analysis, mineral-chemical and microstructural observations, and U-Pb dating. The shear zone developed through a sequence of metamorphic stages: (1) migmatization and granulite-facies metamorphism, (2) eclogite-facies metamorphism, and (3) amphibolite-facies metamorphism. Stage (1) was related to magmatic activity at lower-crustal conditions prior to 1.7 Ga. Stage (2) likely occurred during the early phases of the collision between Baltica and Laurentia (Caledonian collision). Stage (3) was related to shortening during the main phase of the Caledonian collision (-430-400 Ma) and was accompanied by hydration of the shear zone. We demonstrate how mechanical heterogeneities influence the deformation style from the centimeter to meter scale. Zones with a pre-existing fabric deformed by ductile shearing and folding, whereas homogeneous, dry rocks fractured. Fractures provided precursors for small-scale shear zones. These contrasting deformation styles occurred repeatedly. Consequently, pre-existing structures define the deformation style and serve as conduits for the channelization of fluids over extended periods of time.